Psychometric properties of the Czech version of the Beck Anxiety Inventory - comparison between diagnostic groups - Kamaradova, Dana; Prasko, Jan; Latalova, Klara; Panackova, Lucie; Svancara, Jan; Grambal, Ales; Sigmundova, Zuzana; Ociskova, Marie; Bares, Vratislav; Cakirpaloglu, Snezana; Jelenova, Daniela; Kasalova, Petra; et al. (Neuro endocrinology letters, 2015)
OBJECTIVE: Beck anxiety inventory (BAI) is widely used self-rating questionnaire evaluating the severity of anxiety symptoms. The aim of our study was to confirm validity and reliability of Czech version of BAI, identify cut-off points and prove sensitivity to measure improvement after therapy. METHODS: The patients selected for the study were treated in the department of psychiatry, University Hospital Olomouc between January 2008 and 2014. Patients meeting criteria for anxiety, or depressive disorder were involved. RESULTS: 789 patients and 284 healthy controls agreed to participate in the study. Czech version of Beck anxiety inventory proved high internal consistency (α=0.92) and good test-retest reliability over one week (BAI seems to be independent of other used scales - Beck depression inventory and the Clinical Global Impression. BAI is also sensitive to measure change after therapy. CONCLUSION: Czech version of BAI was found to have enough internal stability and test-retest reliability same as the original version. It may also be useful to detect improvement after therapy.